Inhibitory Test of Water Hyacinth Leaf Extract (Eichhornia Crassipes) on the Growth of Escherichia Coli and Propionibacterium Acnes Bacteria - Rumyaan, Yuliana; Helen J. Lawalata; Dany Ch. Posumah; Emma M. Moko; Fernando A. Watung; Nonny Manampiring (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2026)
Antimicrobial resistance has accelerated the search for alternative antibacterial agents derived from natural products. Water hyacinth (Eichhornia crassipes) is an invasive aquatic weed that is abundant in Indonesian waters, yet rich in secondary metabolites such as flavonoids, tannins, alkaloids, and saponins with antibacterial potential. This study aimed to evaluate the inhibitory activity of the ethanol extract of water hyacinth leaves against Escherichia coli (Gram-negative) and Propionibacterium acnes (Gram-positive). A descriptive-exploratory laboratory design was used. Leaf samples collected from Lake Tondano were extracted by maceration in 96% ethanol and concentrated using a rotary evaporator. Antibacterial activity was assessed by the well-diffusion method at 100% extract concentration, with 30% amoxicillin as the comparator, incubated at 37°C for 24 hours. The extract produced mean inhibition zones of 7.0 mm against E. coli and 5.7 mm against P. acnes, both classified as moderate according to the Davis & Stout scheme, whereas amoxicillin produced zones of 8 mm and 7 mm. The ability of the extract to inhibit both Gram-positive and Gram-negative bacteria indicates a broad spectrum of activity. These findings confirm that water hyacinth leaves are a promising source of natural antibacterials while adding value to aquatic weed management.